MIC distributions for amphotericin B, fluconazole, itraconazole, voriconazole, flucytosine and anidulafungin and 35 uncommon pathogenic yeast species from the UK determined using the CLSI broth microdilution method. (5th February 2020) - Borman, Andrew M; Muller, Julian; Walsh-Quantick, Jo; Szekely, Adrien; Patterson, Zoe; Palmer, Michael D; Fraser, Mark; Johnson, Elizabeth M
Abstract: Background: Epidemiological cut-off values and clinical interpretive breakpoints have been developed for a number of antifungal agents with the most common Candida species that account for the majority of infections due to pathogenic yeasts species. However, less-common species, for which susceptibility data are limited, are increasingly reported in high-risk patients and breakthrough infections. Methods: The UK National Mycology Reference Laboratory performs routine antifungal susceptibility testing of clinical yeast isolates submitted from across the UK. Between 2002 and 2016, >32 000 isolates representing 94 different yeast species were referred to the laboratory. Here we present antifungal susceptibility profiles generated over this period for amphotericin B, fluconazole, voriconazole, itraconazole, anidulafungin and flucytosine against 35 species of uncommon yeast using CLSI methodologies. MIC data were interpreted against epidemiological cut-off values and clinical breakpoints developed with Candida albicans, in order to identify species with unusually skewed MIC distributions that potentially indicate resistance. Results: Potential resistance to at least one antifungal agent (>10% of isolates with MICs greater than the epidemiological cut-off or clinical breakpoint) was evidenced for 29/35 species examined here. Four species exhibited elevated MICs with all of the triazole antifungal drugs against which they were tested, and 21 species exhibited antifungal resistance to agents from at least two different classes of antifungal agent. Conclusions: This study highlights a number of yeast species with unusual MIC distributions and provides data to aid clinicians in deciding which antifungal regimens may be appropriate when confronted with infections with rarer yeasts.